EMADDC: high-volume, high-quality, and timely wind and temperature observations from aircraft surveillance data (Mode-S EHS) - S. de Haan; P. de Jong; M. Koutek; J. Sondij; L. Strauss (Atmospheric Measurement Techniques)
Wind and temperature observations from aircraft are of major importance for aviation meteorology and numerical weather prediction (NWP). The European Meteorological Aircraft Derived Data Centre (EMADDC) system processes aircraft surveillance data received from air traffic control (ATC) and other partners and converts them into upper-air observations of wind and temperature. Only so-called Mode-S Enhanced Surveillance (Mode-S EHS) data can be used because these data contain the air vector and ground vector of the aircraft from which a wind vector can be inferred. Temperature is derived from true airspeed and Mach number measurements. To produce high-quality observations, the data are processed in three steps: pre-processing, processing, and post-processing. The pre-processing is needed to obtain high-quality information and to calculate several correction values for correcting temperature observations and heading values. Processing converts the aircraft data into meteorological information, and finally post-processing guarantees that only high-quality information is made available.